Bacterial Outer Membrane Vesicle-Mediated Cytosolic Delivery of Flagellin Triggers Host NLRC4 Canonical Inflammasome Signaling - Yang, Jungmin; Hwang, Inhwa; Lee, Eunju; Shin, Sung Jae; Lee, Eun-Jin; Rhee, Joon Haeng; Yu, Je-Wook (Frontiers in Immunology, 2020)
Bacteria-released components can modulate host innate immune response in the absence of direct host cell–bacteria interaction. In particular, bacteria-derived outer membrane vesicles (OMVs) were recently shown to activate host caspase-11-mediated non-canonical inflammasome pathway via deliverance of OMV-bound lipopolysaccharide. However, further precise understanding of innate immune-modulation by bacterial OMVs remains elusive. Here, we present evidence that flagellated bacteria-released OMVs can trigger NLRC4 canonical inflammasome activation via flagellin delivery to the cytoplasm of host cells. Salmonella typhimurium-derived OMVs caused a robust NLRC4-mediated caspase-1 activation and interleukin-1β secretion in macrophages in an endocytosis-dependent, but guanylate-binding protein-independent manner. Notably, OMV-associated flagellin is crucial for Salmonella OMV-induced inflammasome response. Flagellated Pseudomonas aeruginosa-released OMVs consistently promoted robust NLRC4 inflammasome activation, while non-flagellated Escherichia coli-released OMVs induced NLRC4-independent non-canonical inflammasome activation leading to NLRP3-mediated interleukin-1β secretion. Flagellin-deficient Salmonella OMVs caused a weak interleukin-1β production in a NLRP3-dependent manner. These findings indicate that Salmonella OMV triggers NLRC4 inflammasome activation via OMV-associated flagellin in addition to a mild induction of non-canonical inflammasome signaling via OMV-bound lipopolysaccharide. Intriguingly, flagellated Salmonella-derived OMVs induced more rapid inflammasome response than flagellin-deficient Salmonella OMV and non-flagellated Escherichia coli-derived OMVs. Supporting these in vitro results, Nlrc4-deficient mice showed significantly reduced interleukin-1β production after intraperitoneal challenge with Salmonella-released OMVs. Taken together, our results here propose that NLRC4 inflammasome machinery is a rapid sensor of bacterial OMV-bound flagellin as a host defense mechanism against bacterial pathogen infection.